Clinical and Genomic Characterization of Recurrent Enterococcal Bloodstream Infection in Patients With Acute Leukemia. (5th May 2018) - Messina, Julia A; Sinha, Rohita; Starr, Kimberly; Arshad, Mehreen; Alexander, Barbara D; Chao, Nelson J; Sung, Anthony D
Abstract: Background: Rates and risk factors for recurrent enterococcal bloodstream infection (R-EBSI) and whether the same genetic lineage causes index EBSI and R-EBSI are unknown in patients with acute leukemia (AL) receiving chemotherapy. Methods: Ninety-two AL patients with EBSI from 2010 to 2015 were included. Enterococcal bloodstream infection was defined by 31 positive blood cultures for Enterococcus faecium or Enterococcus faecalis and fever, hypotension, or chills. Clearance was defined by 31 negative cultures 324 hours after last positive culture and defervescence. Recurrent enterococcal bloodstream infection was defined by a positive blood culture for Enterococcus 324 hours after clearance. Categorical variables were reported as proportions and compared by the χ 2 test. Continuous variables were summarized by median and interquartile range (IQR) and compared by the Wilcoxon-Mann-Whitney Test. P values <.05 were considered significant. Whole-genome sequencing was performed on available paired BSI isolates from 7 patients. Results: Twenty-four patients (26%) had 31 episodes of R-EBSI. Median time to R-EBSI (IQR) was 26 (13–50) days. Patients with R-EBSI had significantly longer durations of fever and metronidazole exposure during their index EBSI. Thirty-nine percent of E. faecium R-EBSI isolates became daptomycin-nonsusceptible Enterococcus (DNSE) following daptomycin therapy for index EBSI. Whole-genome sequencing analysis confirmed high probability of genetic relatedness of index EBSI and R-EBSI isolates for 4/7 patients. Conclusions: Recurrent enterococcal bloodstream infection and DNSE are common in patients with AL and tend to occur within the first 30 days of index EBSI. Duration of fever and metronidazole exposure may be useful in determining risk for R-EBSI. Whole-genome sequencing analysis demonstrates that the same strain causes both EBSI and R-EBSI in some patients.